Search for the standard model Higgs boson in the decay channel H→ZZ→4l in pp collisions at √s=7TeV - Chatrchyan, S; Khachatryan, V; Sirunyan, A; Tumasyan, A; Adam, W; Bergauer, T; Dragicevic, M; Erö, J; Fabjan, C; Friedl, M; Frühwirth, R; Ghete, V; et al. (2012)
A search for a Higgs boson in the four-lepton decay channel H→ZZ, with each Z boson decaying to an electron or muon pair, is reported. The search covers Higgs boson mass hypotheses in the range of 110<m -1="" 4-="" 4.7fb="" 600gev.="" an="" analysis="" are="" at="" by="" cms="" collisions="" corresponding="" data="" detector="" events="" four-lepton="" from="" h<="" in="" integrated="" invariant="" lhc.="" luminosity="" m="" mass="" observed="" of="" pp="" recorded="" seventy-two="" the="" to="" uses="" with="" √s="7TeV">100GeV (with 13 below 160GeV), while 67.1±6.0 (9.5±1.3) events are expected from background. The four-lepton mass distribution is consistent with the expectation of standard model background production of ZZ pairs. Upper limits at 95% confidence level exclude the standard model Higgs boson in the ranges of 134-158GeV, 180-305GeV, and 340-465GeV. Small excesses of events are observed around masses of 119, 126, and 320GeV, making the observed limits weaker than expected in the absence of a signal. © 2012 CERN.</m>